2013
DOI: 10.1098/rstb.2013.0073
|View full text |Cite
|
Sign up to set email alerts
|

Female competition and aggression: interdisciplinary perspectives

Abstract: This paper introduces a Theme Issue combining interdisciplinary perspectives in the study of female competition and aggression. Despite a history of being largely overlooked, evidence is now accumulating for the widespread evolutionary significance of female competition. Here, we provide a synthesis of contributions to this Theme Issue on humans and other vertebrates, and highlight directions for future research. Females compete for resources needed to survive and reproduce, and for preferred mates. Although f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
126
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 170 publications
(307 reference statements)
5
126
1
Order By: Relevance
“…Most work on intrasexual competition in humans has focused on direct (i.e., physically aggressive) competition among men (Stockley & Campbell, 2013). Although direct competition among women clearly does occur (Stockley & Campbell, 2013), intrasexual competition among women more commonly takes other forms, such as self-promotion and the derogation of competitors (Vaillancourt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most work on intrasexual competition in humans has focused on direct (i.e., physically aggressive) competition among men (Stockley & Campbell, 2013). Although direct competition among women clearly does occur (Stockley & Campbell, 2013), intrasexual competition among women more commonly takes other forms, such as self-promotion and the derogation of competitors (Vaillancourt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…highly ranked by men as desirable female characteristics, which could contribute to making men more competitive than women over these cash resources. On the contrary, given the different and more important role that mothers play in infant survival (23), and the high costs associated with violence (8), females reserve their most intense competitive behavior to ensure their reproductive success [i.e., the survival and thriving of their offspring (3,5,8)]. Therefore, we expect that women will be relatively more competitive for resources that directly benefit one's offspring than for a cash prize.…”
mentioning
confidence: 99%
“…If competitive traits derive from selection pressures, then men and women should each have evolved competitive traits. Recently, important studies have laid the foundation for understanding the difference in competitive strategies pursued by the sexes and, in particular, found that females reserve their most intense competitive behaviors for the benefit of offspring (3,5,8). The goal of this paper is to contribute new behavioral evidence to the study of the different modalities of women's competition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to classical sex roles, competition among males is evaluated through intrasexual selection, whereas intersexual selection leads to non-random mating because females exercise mate choice to maximize direct or indirect benefits of choosing particular males [53,54]. However, it is now recognized that males are also choosy [55] and that females compete among each other as well [56,57]. Both inter-and intrasexual selection have several direct and indirect consequences for animal health.…”
Section: (A) Society-level Defences Against Infectious Diseasementioning
confidence: 99%